2014
DOI: 10.1002/ep.12070
|View full text |Cite
|
Sign up to set email alerts
|

KF‐impregnated clam shells for biodiesel production and its effect on a diesel engine performance and emission characteristics

Abstract: Natural white bivalve clam shells were calcined to obtain calcium oxide (CaO) and KF/CaO catalyst was synthesized by impregnating potassium fluoride (KF) on calcined clam shells. This solid catalyst was tested for transesterification of waste frying oil. A high biodiesel yield of 95.77% was obtained at methanol/oil molar ratio of 9:1, catalyst amount of 4 wt % (based on oil weight), reaction temperature of 65 C and reaction time of 2 h. The performance and emission characteristics of a single cylinder, four st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…It is observed that specific NOx increases with the increasing percentage share of biodiesel in the blend. Similar trends of NOx for biodiesel blends were also reported in the literature, which were correlated with the fuel bound oxygen content, bulk modulus and degree of hydrocarbon unsaturation (iodine number) of the biodiesel . But in this study the combined effects of some additional fuel and engine parameters on thermal NOx levels are being investigated.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It is observed that specific NOx increases with the increasing percentage share of biodiesel in the blend. Similar trends of NOx for biodiesel blends were also reported in the literature, which were correlated with the fuel bound oxygen content, bulk modulus and degree of hydrocarbon unsaturation (iodine number) of the biodiesel . But in this study the combined effects of some additional fuel and engine parameters on thermal NOx levels are being investigated.…”
Section: Resultssupporting
confidence: 82%
“…It was reported in most of the literature that, NOx levels increase with the use of biodiesel due to their higher oxygen contents [14][15][16][17][18][19]. A few researchers found the opposite trend [20][21][22], negating the idea that biodiesel fuel-bound oxygen increases NOx emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Exergy of air can be neglected. Exergy input can be described by _ E x in 5 _ m fuel E fuel (11) where E fuel is the specific exergy of the fuel and it can be obtained using Eq. (12):…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that biodiesel as pilot fuel exhibits similar pressure-time history, with highest peak, as diesel fuel in conventional and dual fuel modes. Niju et al [11] utilized KF/CaO as a solid catalyst for the transesterification of waste frying oil. The synthesized biodie-sel was blended (B20, B40, B60, and B80) with conventional diesel fuel and the effects of blending on the engine performance and emission characteristics were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The indicted mean effective pressure (IMEP) is a parameter that combines the effects of in‐cylinder pressure and CA on engine output . The coefficient of variation for IMEP (COV IMEP ) is used to evaluate the combustion stability, given by COVnormalIMEP=δnormalIMEPtruenormalIMEP¯×100% where, δ IMEP is the standard deviation of IMEP, and trueIMEP¯ is the mean value of the IMEP of a specific combustion cycle.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%